Promoting tomato resilience: effects of ascorbic acid and sulfur-treated biochar in saline and non-saline cultivation environments - Muhammad Ikram; Asif Minhas; Arwa A. AL-Huqail; Adel M. Ghoneim; Sammina Mahmood; Esawy Mahmoud; Maryam Tahira; Muhammad Mehran; Muhammad Faizan Khurram Maqsood; Abdul Rauf; Waqar Ali (BMC Plant Biology)
Abstract The resilience of tomato plants under different cultivation environments, particularly saline and non-saline conditions, was investigated by applying various treatments, including 0.5% Ascorbic Acid (AsA) and 1% Sulphur-treated Biochar (BS). The study evaluated parameters such as fruit length, diameter, yield per plant and pot, Total Soluble Solids (TSS) content, chlorophyll content, electrolyte leakage, enzyme activities (Superoxide Dismutase - SOD, Peroxidase - POD, Catalase - CAT), and nutrient content (Nitrogen - N%, Phosphorus - P%, Potassium - K%). Under saline conditions, significant enhancements were observed in fruit characteristics and yield metrics with the application of AsA and BS individually, with the combined treatment yielding the most substantial improvements. Notably, AsA and BS treatments exhibited varying effects on TSS levels, chlorophyll content, electrolyte leakage, and enzyme activities, with the combination treatment consistently demonstrating superior outcomes. Additionally, nutrient content analysis revealed notable increases, particularly under non-saline conditions, with the combined treatment showcasing the most significant enhancements. Overall, the study underscores the potential of AsA and BS treatments in promoting tomato resilience, offering insights into their synergistic effects on multiple physiological and biochemical parameters crucial for plant growth and productivity.